Multiple Factors Causing Myopia and the Possible Treatments: A Mini Review - Shinojima, Ari; Negishi, Kazuno; Tsubota, Kazuo; Kurihara, Toshihide (Frontiers in Public Health, 2022)
The epidemic of myopia is a global public health problem. Although myopia is progressing worldwide, the recent corona virus disease 2019 (COVID-19) pandemic has spurred myopia progression. The current evidence-based treatments for humans are atropine eye drops, optical treatment with defocus, use of orthokeratology, longer distance in near work, pausing from near work every 30 min and increased outdoor time. Studies on myopia using animal models have been conducted for more than 40 years. In recent years, new mechanisms of myopia suppression have been revealed from animal experiments such as inflammation control, intraocular pressure control, light control, and the activity of early growth response protein 1 control. This mini-review summarizes the current scientific evidence on myopia control, presents relevant public health issues, and the possible treatments mitigating myopia.